Sensory evaluation on selected food preparations of nostoc commune vaucher (Cyanobacteria) - Martinez-Goss, Milagrosa (Philippine scientist: a scholarly journal for natural and physical sciences and mathematics, 2014)
Four different food formulation of the dried, disk-type, edible cyanobacterium, Nostoc commune Vaucher, locally known as "tab-taba" in the Ilokano dialect, were prepared as vegetable dish (I), pickes (II), dried "dates" (III), and sweetened (IV). Using the Kruskal-Wallis test with the assumption that the data were homogenous, all food preparations with Nostoc were homogenous, all food preparations with Nostoc were found to be independent of each other X=0.05). Types I-IV were subjected to sensory evaluation and comparison of the means by category through graphical representations from type to type (I-IV) determined that the best food preparation was the Nostoc vegetable dish (I) followed by the Nostoc pickes (II).